Enhancing the versatility of alternate current biosusceptometry (ACB) through the synthesis of a dextrose-modified tracer and a magnetic muco-adhesive cellulose gel - Martins, Murillo L. [UNESP]; Calabresi, Marcos Felipe de Freitas [UNESP]; Quini, Caio César [UNESP]; Matos, Juliana F. [UNESP]; Miranda, José R. A. [UNESP]; Saeki, Margarida Juri [UNESP]; Bordallo, Heloisa N. (Elsevier B.V., 2015)
Alternate Current Biosusceptometry (ACB) is a promising bio-magnetic method, radiation free and easily performed used for gastric emptying exams. Due to development on its sensitivity level, interesting nature, noninvasiveness and low cost it has attracted a lot of attention. In this work, magnetic nanoparticles of Mn-Zn ferrite as well as dextrose-modified nanoparticles were synthesized to be used as possible tracers in ACB gastric emptying exams. In addition, a magnetic muco-adhesive gel was obtained by modifying the ferrite nanoparticles with cellulose. Based on in-vivo tests in rats, we show that the pure ferrite nanoparticles, whose isoelectric point was found to be at pH = 3.2, present a great sensitivity to pH variations along the gastrointestinal tract, while the reduction of the isoelectric point by the dextrose modification leads to suitable nanoparticles for rapid gastric emptying examinations. On the other hand, the in-vivo tests show that the muco-adhesive cellulose gel presents substantial stomach adhesion and is a potential drug delivery system easily traceable by the ACB system. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Alternate current biosusceptometry; Gastric emptying; Bio-magnetic materials; Muco-adhesive gel; Cellulose; Dextrose